3D bioprinted extracellular vesicles for tissue engineering—a perspective. (1st January 2023) - Han, Pingping; Ivanovski, Sašo
Abstract: Harnessing three-dimensional (3D) bioprinted extracellular vesicles (EVs) holds great promise for advancing the fields of tissue engineering and regenerative medicine. EVs are naturally occurring biological nanoparticles that are emerging as powerful 'cell-free' nanotherapeutics characterized by a cargo of protein, lipids, or genetic material that can be delivered to recipient cells. Conventional 3D bioprinting utilizes bioinks, a mixture of biomaterial and live cells, to fabricate 3D constructs for tissue regeneration purposes. The utilization of EVs instead of living cells for bioprinting may achieve targeted EV delivery, thus addressing a key challenge of EVs application in tissue engineering, as well as overcoming the regulatory and cost-effectiveness issues of using live cells. Given that 3D bioprinted EVs combine the regenerative capabilities of both bioprinting and EVs, this perspective explores the existing literature reporting their applications in tissue engineering, which target angiogenesis, osteogenesis, chondrogenesis, myogenesis, and carcinoprevention. Technical challenges and future trends for 3D bioprinted EVs in biofabrication and tissue engineering are examined. Ultimately, a personalized bioprinted EVs concept and a workflow for future bioprinted EVs studies focussed on clinical translation are proposed.